Infrared microscopy studies of the chemical composition of latent fingermark residues - Fritz, Patrick; Van Bronswijk, Wilhelm; Lepkova, Katerina; Lewis, Simon; Lim, K.; Martin, D.; Puskar, L. (Elsevier, 2013)
Synchrotron-infrared microscopy provides a non-destructive technique to investigate the chemical composition of latent fingermarks in-situ. The high spatial resolution and brightness of the synchrotron source also lends itself to the chemical characterisation of trace amounts of material on surfaces. However, only the lipid fraction of fingermark deposits is targeted when transmission-reflection is used. The fingermark lipid residues appeared to be relatively homogenous in composition across the deposit for any particular donor. No significant variation in the lipid composition as a function of age or gender of the donor was observed.Investigations into fingermark degradation were carried out by collecting spectra from fingermarks at three month intervals. An overall decrease in signal intensity was observed, ascribed to evaporation of the fingermark deposit. Greatest loss of material appeared to occur during the first 3 months following deposition. However, no significant variation in lipid composition was detected over a 9-month period.The outcomes of this study indicate that latent fingermark visualisation reagents that target lipids should produce accurate and reliable renditions of fingermarks irrespective of the age or gender of the donor, albeit with reduced sensitivity as the fingermark ages.